Pendidikan Agama Kristen Serta Kurikulumnya Dalam Menanggapi AI - Sutarman Laia; Susiana Lase; Karsa Krisman Gulo; Lisna Novalia (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2024)
The rapid development of artificial intelligence (AI) presents new challenges and opportunities in various fields, including in Christian religious education. This article discusses how Christian Religious Education (PAK) and its curriculum can respond to the dynamics presented by AI technology. This article uses a descriptive qualitative method based on literature and scientific journals. The main sources of this research are taken from various literature and scientific journals that are relevant to the research topic. The main focus lies in the adjustment of learning materials that are relevant to the needs of the times, the formation of Christian ethics in the digital era, and the importance of maintaining spiritual values ​​amidst technological developments. The use of Artificial Intelligence (AI) in PAK still adheres to the principles of Christian ethics and values. Theological understanding of the role of humans, morality, and their relationship with the creator is described in the perspective of Christian ethics towards artificial intelligence (AI). The Role of Humans in the Process of Christian Religious Education related to the application of AI involves deep reflection on the relationship between Bible verses and the implementation of artificial intelligence in religious education. In addition, this article explores the potential use of AI in the learning process, such as through personalization of education and increasing interaction between teachers and students. It is hoped that with proper adaptation, PAK can remain relevant and provide a solid foundation of faith for future generations in facing the challenges of modern technology.